4‐H Healthy Living programs with impact: A national environmental scan. Issue 143 (September 2014) - Downey, Laura H.; Peterson, Donna J.; LeMenestrel, Suzanne; Leatherman, JoAnne; Lang, James
Abstract : The 4‐H youth development program of the nation's 109 land‐grant universities and the Cooperative Extension System is one of the largest youth development organization in the United States serving approximately six million youth. The 4‐H Healthy Living initiative began in 2008 to promote achievement of optimal physical, social, and emotional well‐being for youth and families. In 2013, the National 4‐H Council sought to identify 4‐H Healthy Living programs in the domains of healthy eating and physical activity that adhered to the national 4‐H Healthy Living mission and were ready for comprehensive outcome evaluation or replication at a national level. This chapter shares findings from an environmental scan of 4‐H programs and (a) identifies programs with evidence of promoting a healthy diet and physical activity, (b) describes program impacts related to healthy diet and physical activity, and (c) clarifies select program characteristics associated with reported healthy eating and/or physical activity outcomes. The RE‐AIM evaluation framework is introduced as an effective approach to assessing program impact for 4‐H Healthy Living and similar out‐of‐school time programs.